Influence of physical activity home environment on fundamental movement skills development in Chinese preschoolers: mediating role of moderate-to-vigorous physical activity - Liu, Pan; Fan, Chengwen; Li, Fang; Yang, Zongyu; Yang, Bin; Yin, Long (Frontiers in Pediatrics, 2024)
Background: Research on how the physical activity home environment affects fundamental movement skills (FMS) in preschool children in China is limited. However, the role of moderate-to-vigorous physical activity (MVPA) in this relationship is still unclear. This study aims to analyze gender differences in FMS, explore associations between the physical activity home environment, MVPA, and FMS, and investigate MVPA's mediating role in these relationships. Methods: We recruited 169 preschool children (95 boys, 74 girls; mean age 4.9 years) from four kindergartens in Hengyang, China. The Family Environment Scale on Motor Development for Preschool Urban Children (FESMPD) assessed the sports environment within the family unit. Objective measurement of MVPA used ActiGraph wGT3-BT accelerometers. The Test of Gross Motor Development-3 (TGMD-3) evaluated FMS. Statistical analyses were conducted using the PROCESS macro in SPSS, with sociodemographic variables as controls.Results: Boys exhibited significantly higher levels of MVPA, parenting style, locomotor skills, and object control skills compared to girls (P<0.05). MVPA, parenting style, and FMS showed positive correlations (R=0.355-0.568, P<0.05). Similarly, MVPA was positively correlated with the physical activity home environment (β=0.237-0.568,P<0.05). Parenting style emerged as a significant predictor of children's MVPA levels (β=0.956, P<0.001), and MVPA was a predictor of the development of FMS and its subdomains (β=0.097-0.207, P<0.05). Furthermore, MVPA partially mediated the relationship between parenting style and the development of FMS in preschool children. The physical environment was also a significant predictor of children's MVPA (β=0.637, P<0.05), and in turn, MVPA predicted the development of FMS and its subdomains (β=0.188-0.343, P<0.01). Notably, MVPA fully mediated the relationship between the physical environment and the development of FMS.Overall, this study highlights the important roles of physical activity home environments and individual levels of MVPA in developing FMS in preschool children, noting significant gender differences. Parenting style greatly affects both MVPA and FMS development, while the physical environment fully mediates this relationship.Collaborative efforts among kindergartens, families, and communities are essential to support MVPA and improve FMS development.